Muscle-Specific Tyrosine Kinase-Associated Myasthenia Gravis: A Neuromuscular Surprise - Hassam Ali; Rahul Pamarthy; Nayab Ahsan; null WashmaAwan; Shiza Sarfraz (Case Reports in Neurological Medicine)
Myasthenia gravis is a neuromuscular autoimmune disease that results in skeletal muscle weakness that worsens after periods of activity and improves after rest. Myasthenia gravis means “grave (serious), muscle weakness.” Although not completely curable, it can be managed well with a relatively high quality of life and expectancy. In myasthenia gravis, antibodies against the acetylcholine receptors at the neuromuscular junction interfere with regular muscular contraction. Although most commonly caused by antibodies to the acetylcholine receptor, antibodies against MuSK (muscle-specific kinase) protein can also weaken transmission at the neuromuscular junction. Muscle-specific tyrosine kinase myasthenia gravis (MuSK-Ab MG) is a rare subtype of myasthenia gravis with distinct pathogenesis and unique clinical features. Diagnosis can be challenging due to its atypical presentation as compared to seropositive myasthenia gravis. It responds inconsistently to steroids, but plasma exchange and immunosuppressive therapies have shown promising results. We report a case of a 49-year-old female who presented with acute hypoxic respiratory failure. Our patient experienced progressive, undiagnosed MuSK-Ab MG for years without a diagnosis.